Characterization of defects of mullite fibers prepared by polyvinyl butyral as spinning aid - Zhang Y.B.; Xiao C.F.; An S.L.; Yang J.F.; Xu S.J. (Science of Sintering, 2010)
Mullite fibers have been synthesized using polyvinyl butyral as spinning aids. Defects including cracks, core-sheath structure, randomly arranged powders, shots and rough surface were observed. The results showed that circumferential cracks were terminated by the main axial crack. The thermal shrinkage could be considered as the reason for the formation of cracks and core-sheath structure. Improper control of heat treatment resulted in the rough surface around fibers. The wet gel fibers were easily inserted by some alumina powders which were used to obtain the uniform shrinkage during calcinations in the kiln.